IMPLEMENTASI KEBIJAKAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN JATINANGOR KABUPATEN SUMEDANG PROVINSI JAWA BARAT - Febryansyah Pratama Putra; Teresa Irmina Nangameka (Institut Pemerintahan Dalam Negeri, 2018)
ABSTRACT Sub-District as one of the autonomous regional tools is expected to contribute greatly in providing services to the community. In order to meet the needs of the community to obtain easy, fast and appropriate services at the sub-district level, the government rolled out the Sub-District Integrated Service Administration Program (PATEN) with the issuance of Regulation of the Minister of Home Affairs Number 4 Year 2010 concerning the Guidelines for District Integrated Administration Service. To that end, the writer are interested in conducting research with the title “The Implementation of SubDistrict Integrated Service Administration Policy (Paten) in Jatinangor Sub District Sumedang Region West Java Province”. This research is focused on analyzing the Implementation of Sub-District Integrated Service Administration (PATEN), analyzing the inhibiting factors in the implementation of PATEN, and knowing what efforts to improve the implementation of PATEN in Jatinangor Sub-district, Sumedang Region. The research method that is used in the writing of this thesis is a qualitative research method with descriptive approach which is processed begins by declaring the statement with a unique and limited scope to be analyzed and draw conclusions on the problems that occur. Data collection techniques that used are interviews, documentation, and observation. Edward III’s theory as the implementation theory that is used in this research shows the result that the implementation of PATEN policy in Jatinangor Sub-district has been running well. However, there are still some inhibiting factors such as the far distance of sub-district from the district capital, insufficient facilities and infrastructure, lack of socialization among the younger generation, and there are some unfill position that can support the implementation of PATEN. The efforts undertaken in order to improve the implementation of PATEN policy in Jatinangor Sub-District is to further promote e-Government as part of coordination with the district government, adding some facilities and infrastructure that support implementation of PATEN, providing good model of PATEN socialization that is acceptable to all circles, and involving the Sub-District apparatus in some Training and Technical Guidance activities. Keywords: policy implementation, administration services, PATEN.